Les différentes représentations et symboliques du cheval à travers l’iconographie de la région de Cirta du Ier à la fin du IIIe siècle après J.-C. - Amandine Cristina; Emmanuelle Lechilli (In Situ)
Representations and symbolisms of the horse in the iconography of the Cirta region, first to third centuries A.D. The region of Cirta corresponds with the present-day area of North-East Algeria. It is a region which has always had the reputation of being a privileged one, its prosperity based on agriculture and livestock breeding. The animals of the region are known through its written and iconographical sources, in which the horse plays an important part. However, although different uses of the horse are represented in various media, it was more often the horse’s symbolic characteristics that were highlighted. From a corpus of representations of Cirtean horses we will show examples to suggest that the way the horse is represented, in its different functions and attitudes, depends primarily on the medium in which it featured. To understand the choice of medium, it is necessary, too, to appreciate the horse’s symbolic aspects.